تبلیغی جماعت کے ذرائع تبلیغ کا تحقیقی جائزہ (Al-Qamar, 2024)
Preaching of Islam is the most important responsibility of Ummah. For the payment of this duty various missionary organizations were established in the Muslim world. Tablighi Jammat is also a Tablighi movement, which was established by Maulana Muhammad Ilyas. Because the Maio nation was in danger of apostasy, this requires a Tablighi Jammat occurred. Now this movement is active in many countries of the world. Tablighi Jammat has own ways and timing course for preaching. They use different ways to preach. They preach through speeches, letters. They also send Tablighi deputations to entire country and outside countries for preaching. Besides male parties’ female parties also send. On the other hand, they use modern resources for preaching such as TV, Internet, Laptop, videos and audios etc. These means easy and useful to conveying the message of Islam.
Keywords: Lecturer; Islamic Studies; Govt. Degree Boys College Manghopir; Karachi